IDENTIFICATION OF ALKALIMETRIC LEVELS USING ACID-BASE REACTION PRINCIPLES - Dianingsi Hipi; Eka Paramita Daud; Gayatri D. Soga (LPPM Universitas Bina Mandiri Gorontalo, 2021)
Acidimetry is a titration using a standard solution of an acid to determine a base. The acids that are usually used are HCl, vinegar, oxalic acid, boric acid. While alkalimetry is the opposite of acidimetry, which is a titration that uses a standard solution of a base to determine acid.This study aims to identify the substance in a sample and determine the level is the principle of acid-base reactions. Acidi-alkalimetric titration is a volumetric titration using NaOH as the secondary standard solution and potassium hydrogen phthalate as the primary standard solution and added pp indicator. The end point of the titration is indicated by a change in the color of the solution to a pink color. Alkalimetry is a quantitative determination of the levels of compounds that are acidic by using a standard base. The method used is the experimental method through a quantitative approach. The research method is used to determine the effect of the independent variable or treatment on the dependent or the results under controlled conditions. The results of the study obtained the calculation of the volume of NaOH 28.7 then performed in duplicate to obtain the calculation of the volume of NaOH 29.7. So the calculation of the concentration of Salicylic Acid is0,584 M.